2004
DOI: 10.1677/jme.0.0320365
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nuclear factor kappa B in the regulation of rat luteal function: potential roles as survival factor and inhibitor of 20alpha-hydroxysteroid dehydrogenase

Abstract: Nuclear factor kappa B (NF B) is an important intracellular conveyor of extracellular signals and modulates a number of gene responses. Due to the potential significance of NF B in regulating ovarian gene expression, we examined in the rat: (i) whether NF B is activated and developmentally regulated in the corpus luteum (CL) throughout pregnancy; (ii) the proteins forming the NF B complex in luteal cells; and (iii) the role of this transcription factor in luteal function. Western analysis and immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In addition, helenalin interacts with RelA to inhibit DNA binding to its cognate response elements and by inhibiting activation of the transcription factor NF-κB [7]. Blockade of NF-κB/p65 binding to DNA with helenalin correlated with induction of cell death in a dose-dependent manner [14]. Numerous reports have demonstrated NF-κB p65 to play a role in autophagy induced cell death [13,15], however the function in which helenalin participated in autophagy was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, helenalin interacts with RelA to inhibit DNA binding to its cognate response elements and by inhibiting activation of the transcription factor NF-κB [7]. Blockade of NF-κB/p65 binding to DNA with helenalin correlated with induction of cell death in a dose-dependent manner [14]. Numerous reports have demonstrated NF-κB p65 to play a role in autophagy induced cell death [13,15], however the function in which helenalin participated in autophagy was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…First, why is the transcription of mcp-1 gene not induced before culturing in luteal cells where NF-kB is already active? Other investigators have also reported the presence of active NF-kB in rat luteal cells (Telleria et al, 2004). A likely explanation for this is that NF-kB is necessary but not sufficient for the activation of JNK.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, NF‐κB is closed with the inflammatory response through interleukin (IL)‐1β production (Wu et al, ; Yang et al, ), including ovarian grannulosa cells (Yang et al, ). Some reports demonstrated NF‐κB was expressed in human granulosa luteal cells and activated by TNF‐α, resulting in degradation of IκBalpha and mobilization of NF‐κB into the nucleus (Gonzalez‐Navarrete et al, ), and NF‐κB was also involved in the regulation of rat luteal function as a survival factor and inhibitor of 20alpha‐hydroxysteroid dehydrogenase (Telleria et al, ). Interestingly, NF‐κB was implicated for angiogenesis of corpus luteum and ovarian hyperstimulation syndrome (Chen et al, ), which was consistent with the role of HIF‐1α signaling (Zhang et al, , b, ).…”
Section: Discussionmentioning
confidence: 99%